If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3y+2)=16
We move all terms to the left:
2(3y+2)-(16)=0
We multiply parentheses
6y+4-16=0
We add all the numbers together, and all the variables
6y-12=0
We move all terms containing y to the left, all other terms to the right
6y=12
y=12/6
y=2
| 8c=9c+5 | | 2-1/2n=3n+6 | | -5g=-10g+10 | | 13+p/7=-5 | | 4=3(x-5)+2-2x | | 52x-52=13(4x-4) | | G24+n/4=10 | | 5q=7q-10 | | c=39.42+0.50 | | 10(x-15)=70 | | 34=5(x+8)-7x | | (8/15)q^2-100q+Y=0 | | 10x+17x-6+5=-8x+5-6 | | 4v+42=-2(v-6) | | x-12.08=4.22 | | 33(x-1.25)=11.25 | | 4/x=6/2.1 | | 110=38.08+0.25x | | 2x/x^2=2/x+1-1/x-1 | | 7x-8=9x-8 | | 5x/3-4=1 | | 144-x=0 | | 5=9+c/4 | | 12.75=x+1.375x | | X+2(x-7=4 | | 9/81=22/x | | f(9)=9 | | x-3-1/4x=x+12-1x | | 17=9−2*a | | 3g+4(-6+3)=1-g | | 40+d=-20-4d | | (3-x-)6=24 |